THE EFFECT OF XYLITOL-BASED ORAL HYGIENE PRODUCTS ON SALIVA PARAMETERS AND BACTERIAL BIOFILM CARIOACTIVITY - Galina Pancu; Sorin Andrian; Simona Stoleriu; Angela Gheorghe; Irina Nica; Claudiu Topoliceanu; Moldovanu Antonia; Nicoleta Tofan; Gianina Iovan (Romanian Society of Oral Rehabilitation, 2017)
Xylitol is a natural polyol, used as saccharine replacer and noncariogenic edulcorant, promoting the remineralisation both by the increasing of saliva rate and inhibition of bacteria growth. Despite these anticariogenic properties, the proofs related to clinical effectiveness of xylitol are controversial. The aim of study The aim of this study is to assess the effect of xyilitol from oral hygiene products (toothpastes, mouthwashes, chewing gums) on the saliva parameters (saliva microcrystallisation index (IMK), saliva resting flow rate (RFR), saliva stimulated flow rate (SFR), saliva buffering capacity (BC)) and the carioactivity of bacteria biofilm (ATP) for patients with medium cariogenic risk. Material and metods: The study group included 12 patients with medium cariogenic risk, submitted to the use of oral hygiene products xylitol-based for three weeks (toothpastes, mouthwashes, chewing gums). The following parameters were assessed before and after the use of xylitol-based products: saliva microcrystallisation index (IMK), saliva resting flow rate (RFR), saliva stimulated flow rate (SFR), saliva buffering capacity (BC), bacterial biofilm activity (ATP). Results and discution: The results show the significant improving of salivary parameters (IMK, RFR, SFR, BC) and the decrease of ATP levels after the use of xylitol-based oral hygiene products for three weeks Conclusions: The use of xylitol-based products in oral hygiene is effective both in the improvement of salivary parameters and the decrease of bacterial biofilm activity for patients with high cariogenic risk